New experimental setup for the measurement of cleaning efficacy and force of interdental aids in 3D-reproduced interdental areas - Christian Graetz; Johanna Rabe; Kristina Schoepke; Susanne Schorr; Antje Geiken; David Christofzik; Thomas Rinder; Christof E. Dörfer; Sonja Sälzer (BMC, 2020)
Abstract Background Interdental rubber picks (IRP) have become a frequent and convenient alternative for interdental cleaning. However, only little evidence exists supporting the effectiveness of newer designs available on the market. Therefore, a new in vitro model was evaluated to measure the experimental cleaning efficacy (ECE), as well as the force needed for insertion and during the use of IRP, with high reproducibility. Methods Five different sizes of commercially marketed IRP with elastomeric fingers (IRP-F) (GUM SOFT-PICKS® Advanced, Sunstar Deutschland GmbH, Schönau, Germany) or slats (IRP-S) (TePe EasyPick™, TePe D-A-CH GmbH, Hamburg, Germany) were tested. Interdental tooth surfaces were reproduced by a 3D-printer (Form 2, Formlabs Sommerville, MA, USA) according to human teeth and matched to morphologically equivalent pairs (isosceles triangle, concave, convex) fitting to different gap sizes (1.0 mm, 1.1 mm, 1.3 mm). The pre−/post brushing situations at interdental areas (standardized cleaning, computer aided ten cycles) were photographically recorded and quantified by digital image subtraction to calculate ECE [%]. Forces were registered with a load cell [N]. Results IRP-F have to be inserted with significant higher forces of 3.2 ± 1.8 N compared to IRP-S (2.0 ± 1.6 N; p < 0.001) independent of the size and type of artificial interdental area. During cleaning process IRP-S showed significantly lower values for pushing/pulling (1.0 ± 0.8 N/0.5 ± 0.4 N) compared to IRP-F (1.6 ± 0.8 N/0.7 ± 0.3 N; p < 0.001) concomitant to significantly lower ECE (19.1 ± 9.8 vs. 21.7 ± 10.0%, p = 0.002). Highest ECE was measured with largest size of IRP-F/IRP-S independent the morphology of interdental area. Conclusions New interdental cleaning aids can be tested by the new experimental setup supported by 3D printing technology. Within the limitations of an in vitro study, IRP-F cleaned more effectively at higher forces compared to IRP-S.